PRAG1 Condensation Drives Cell Contraction Under Stress - Peiwu Ye; Peiran Jiang; Luyu Ye; Min Liu; Qiuyuan Fang; Peilin Yu; Jianhong Luo; Huanxing Su; Wei Yang (Biomolecules)
Peak1-related, kinase-activating pseudokinase 1 (PRAG1), a member of the pseudopodium-enriched atypical kinase (PEAK) family of pseudokinases, has been reported to play a role in regulating cell morphology. However, the molecular mechanism for this function remains elusive. In this study, we demonstrate that PRAG1 forms dynamic condensates in cells mediated by its αN and αJ helices. Importantly, we found that PRAG1 condensates functioned in mediating cell contraction, while condensate-formation-deficient PRAG1 mutants lost this function. Remarkably, the formation of spherical PRAG1 condensates appears to be a common phenomenon in diverse stress models, as well as in dopaminergic (DA) neurons derived from a Parkinson’s disease patient. Our findings reveal a novel mechanism through which PRAG1 drives cell contraction and suggest a potential link between aberrant PRAG1 phase separation and stress-induced cell contraction. PRAG1 condensation drives cell contraction under stress.